Loss of Function of Fatty Acid Desaturase 7 in Tomato Enhances Photosynthetic Carbon Fixation Efficiency - Wickramanayake, Janithri S.; Goss, Josue A.; Zou, Min; Goggin, Fiona L. (Frontiers in Plant Science, 2020)
Fatty Acid Desaturase 7 (FAD7) generates polyunsaturated fatty acids, promoting the desaturation of chloroplast membranes; it also provides an essential precursor for the synthesis of jasmonic acid (JA), a phytohormone that can influence plant growth, development, and primary metabolism. This study examined the effects of spr2, a null mutation in SlFAD7, on the growth, morphology, and photosynthetic traits of tomato, Solanum lycopersicum. Although the spr2 mutant had a lower density of stomata than wild-type plants, the two genotypes had comparable stomatal conductance, transpiration rates, and intracellular CO2 levels; in addition, spr2 had significantly thinner leaf blades, which may help maintain normal levels of CO2 diffusion despite the lower number of stomata. Surprisingly, spr2 also had significantly higher carbon assimilation (A) and maximum quantum efficiency of PSII (Fv/Fm) than wild type plants at both of the light intensities tested here (220 or 440 µmol m-2 s-1), despite having lower levels of chlorophyll than wild-type plants under low light (220 µmol m-2 s-1). Furthermore, CO2 response curves indicated higher in vivo Rubisco activity (Vcmax) in spr2 compared to wild type plants, as well as an enhanced maximum rate of electron transport used in the regeneration of ribulose-1,5-bisphosphate (Jmax). These data indicate that loss of function of FAD7 can enhance the efficiency of both light-dependent and light-independent reactions in photosynthesis. Consistent with this, the spr2 mutant also displayed enhanced growth, with significantly more leaves and a more compact growth habit. In contrast to spr2, another tomato mutant impaired in JA synthesis (acx1) showed no enhancements in growth or photosynthetic efficiency, suggesting that the enhancements observed in spr2 are independent of the effects of this mutation on JA synthesis. These data demonstrate that loss of function of FAD7 can enhance photosynthesis and growth, potentially through its impacts on the chloroplast membranes.